Testing differences in thermal tolerance between two amphibians with contrasting invasion abilities - VanDenBerg, Evelyn R.; Jaynes, Kyle E.; Shah, Alisha A. (Frontiers in Ecology and Evolution, 2025)
Physiological traits may influence the establishment success of non-native species, yet empirical links between physiology and invasiveness remain limited. The American bullfrog (L. catesbeianus) and the green frog (L. clamitans) are closely related species with overlapping native ranges in the eastern United States, but have contrasting invasion histories: bullfrogs have colonized much of the western U.S., while green frogs have not. One hypothesis that could explain this pattern is that invasive species possess greater tolerance to heat stress and enhanced capacity for thermal acclimation. To test this hypothesis, we compared critical thermal maximum (CTMAX) and acclimation capacity in tadpoles of both species from within their native range. We found that the species both exhibit equally high CTMAX. Further, neither species was able to acclimate to a warmer temperature. However, while bullfrogs showed no change in CTMAX after acclimation, green frogs experienced a slight reduction in CTMAX, suggesting that they may be more sensitive to warming than bullfrogs. These results suggest that intrinsic differences in thermal tolerance and plasticity alone do not explain bullfrog invasion success. Other factors—such as competitive dominance, rapid evolutionary shifts, or interacting abiotic and biotic pressures—may facilitate bullfrog persistence in novel, warmer habitats of the western U.S.